The Impact of STEM Acitivities on Computational Thinking Skills: A Case of Pre Service Elementary School Teachers in Universitas Lampung - Loliyana, Loliyana; Sukamto, Ismu; Astuti, Nelly; Surahman, Maman (Jurnal Pendidikan MIPA, 2022)
The research purpose was to implement of the STEM 4.0 approach in improving student CT. This study used a quasi-experimental design with one group pretest - posttest design. The learning integrated 4 STEM components to improve students’ CT. Participants were elementary school teacher education students at state universities in Lampung Province. The test instrument is at the cognitive level C4 and C6 which refers to Bloom's Taxonomy. Based on research data, it is stated that in learning with the STEM 4.0 approach, there are activities to understand the concept of learning material (Science) by integrating everyday life phenomena (Mathematics) and supported by learning media (Technology). Furthermore, there are learning activities in the form of practice activities in solving a problem in groups and making simple products by applying the concepts contained in the learning materials. Through this treatment, CT participants increased with male CT participants being higher than female. Keywords: computational thinking, STEM approach, pre-service elementary school teacher. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp733-739